2007
DOI: 10.1097/cmr.0b013e3282ef415b
|View full text |Cite
|
Sign up to set email alerts
|

The single-photon emission computed tomography/computed tomography: a new procedure to perform the sentinel node biopsy in patients with head and neck melanoma

Abstract: The aim of this study was to define and validate a new technique to detect the sentinel node (SN) in patients treated for head and neck melanoma. In a small series of 23 head and neck melanoma patients, lymphatic mapping was followed by SN biopsy, using in 12 patients a new diagnostic imaging technique, single-photon emission computed tomography/computed tomography. The procedure is described and the major problems encountered are discussed. The preliminary data show that identification of SN using single-phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 24 publications
(30 reference statements)
0
24
0
Order By: Relevance
“…Figure 2 shows an example of a patient with complex drainage on the conventional images in whom SPECT/CT identified an additional subcutaneous sentinel node underneath the injection area. The value of SPECT/CT for lymphatic mapping of melanoma of the head and neck is underlined by Covarelli et al [34], who demonstrated that sentinel node biopsy based on SPECT/CT images took significantly less time than sentinel node biopsy based on conventional images. The authors argue that more precise preoperative localization of a sentinel node and knowledge of the relationship with anatomical structures facilitated surgical excision [34].…”
Section: Journal Of Surgical Oncologymentioning
confidence: 98%
See 4 more Smart Citations
“…Figure 2 shows an example of a patient with complex drainage on the conventional images in whom SPECT/CT identified an additional subcutaneous sentinel node underneath the injection area. The value of SPECT/CT for lymphatic mapping of melanoma of the head and neck is underlined by Covarelli et al [34], who demonstrated that sentinel node biopsy based on SPECT/CT images took significantly less time than sentinel node biopsy based on conventional images. The authors argue that more precise preoperative localization of a sentinel node and knowledge of the relationship with anatomical structures facilitated surgical excision [34].…”
Section: Journal Of Surgical Oncologymentioning
confidence: 98%
“…The value of SPECT/CT for lymphatic mapping of melanoma of the head and neck is underlined by Covarelli et al [34], who demonstrated that sentinel node biopsy based on SPECT/CT images took significantly less time than sentinel node biopsy based on conventional images. The authors argue that more precise preoperative localization of a sentinel node and knowledge of the relationship with anatomical structures facilitated surgical excision [34]. They also mention that SPECT/CT can detect sentinel nodes in spite of scattered radiation of the injection site.…”
Section: Journal Of Surgical Oncologymentioning
confidence: 98%
See 3 more Smart Citations